(untitled) (Pregled: časopis za društvena pitanja / Periodical for social issues, 2017)
Max Weber is the most significant single scientist in the development of sociology. His basic method is the method of understanding. The first part of the text indicates his view of the relationship between art, eroticism, science and religion. The second part contains an interpretation of comparative framework of his research through the consequent consideration of theodicy. The third part shows the specifics of Weber’s comparative approach. The fourth section shows the role of ideal types in Weber’s "sociology of understanding". The next section shows a method of creating and applying experiential base in his study of world religions. The conclusion is that Weber built partial images into the general framework of ideal types to come to a complete historical knowledge about the culture, applying consistently methodological position that he developed between 1903 and 1907.